Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Impact of diagenesis and acidic alteration on microbial fabrics and trace element distributions in fossilised siliceous hot spring deposits - Barbara J. Lyon; Michael C. Rowe; Andrew Langendam; Kathleen A. Campbell; Diego M. Guido; Ayrton R. Hamilton; Ema E. Nersezova; Amanda Galar; Dominique A. Stallard (Geochimica et Cosmochimica Acta, 2026)

Estimating mercury exposure in amphibians using non-lethal tissue sampling - Caitlin T. Rumrill; Kelly L. Smalling; Colleen Emery; Blake R. Hossack; Brian J. Halstead; Michael J. Adams; Adam R. Backlin; Adrianne B. Brand; Jon M. Davenport; Robert N. Fisher; Jill Fleming; Brad M. Glorioso; et al. (Ecotoxicology, 2026)

Geochronology and mineral geochemistry of apatite and zircon in the Hutouya Skarn deposit, East Kunlun Mountains, NW China - Hongying Qu; Julie Rowland; Jingwen Mao; Ivan Belousov; Evan Orovan; Michael Rowe; Shihua Zhong; Yitian Wang (Mineralogy and Petrology, 2026)

Genomics Reveals Extensive Population Structure and Undescribed Phylogenetic Relationships in the Cascade Torrent Salamander ( Rhyacotriton cascadae ) - Christopher D. Cousins; Deanna H. Olson; Lindsay S. Millward; Michael J. Adams; Christopher A. Pearl; Jennifer C. Rowe; Tiffany S. Garcia (Journal of Biogeography, 2026)
Aim Aims of the study are to examine patterns of range‐wide genetic differentiation and population structure in a headwater obligate salamander living in a geologically rich region, to identify genetically distinct populations and areas of gene flow between them. Location Oregon and Washington in the Pacific Northwest, United States of America. Time Period Tissue samples were collected in 2022 and 2023. Major Taxa Studied The Cascade torrent salamander Rhyacotriton cascadae . Methods Utilisation of a genome‐wide single nucleotide polymorphism (SNP) dataset from across the species range to conduct a principal components analysis (PCA), Bayesian model of population structure, co‐ancestry matrix, phylogenetic tree and estimate genetic diversity. Results There are extensive levels of population structure within R. cascadae , including a previously unknown and highly differentiated clade. Structure is characterised by an island‐like pattern wherein the species is comprised of six populations that function as independent demographic units, with gene flow largely constrained within populations. Main Conclusions Our findings reveal cryptic population structure within R. cascadae , identifying six distinct populations across the range. The northernmost population in the northwest of the species range in Washington is surprisingly highly divergent from the other five populations, and the divergence was not previously known to science. While major rivers act as phylogeographic boundaries between some populations, these boundaries appear to not always be complete.

A 150,000-year lacustrine record of the Indo-Australian monsoon from northern Australia - Michael I. Bird; Michael Brand; Rainy Comley; Xennephone Hadeen; Zenobia Jacobs; Cassandra Rowe; Frédérik Saltré; Christopher M. Wurster; Costijn Zwart; Corey J.A. Bradshaw (Quaternary Science Reviews, 2025)

Holocene hydroclimate inferred from alkane isotope and pollen records from monsoonal northern Australia - Michael I. Bird; Michael Brand; Rainy Comley; Xennephone Hadeen; Niels C. Munksgaard; Cassandra Rowe; Christopher M. Wurster; Costijn Zwart (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Holocene climate changes in tropical Australasia based on branched tetraether lipid evidence from Girraween Lagoon, northern Australia - Weiwei Sun; Enlou Zhang; Cassandra Rowe; Michael I. Bird (CATENA, 2025)

El Zorro: early Jurassic intrusion-related gold (IRG) mineralization in the oldest, western-most segment of the Andean Cordillera of Northern Chile - Eduardo Fritis; Nicholas H. S. Oliver; Michael C. Rowe; Julie V. Rowland; Zeffron C. Reeves; Huiqing Huang (Mineralium Deposita, 2025)
The El Zorro gold district is the most recent gold discovery in the Coastal Cordillera of northern Chile. Ternera is the largest deposit in the district with total resources currently estimated at 1.282 Moz. New geology, geochemistry and geochronology data indicate that hydrothermal mineralization is mostly hosted within felsic to intermediate, ilmenite-bearing calc-alkaline dikes and stocks of the Upper Triassic to Lower Jurassic Relincho Pluton, and some of the adjacent Devonian to Carboniferous metasediments of the Chañaral Epimetamorphic Complex. Sheeted veins, veinlets, and fault zones with quartz, low amounts of pyrite, pyrrhotite and arsenopyrite, and local calcite are surrounded by narrow haloes of albite-biotite-quartz ± sulfides-K-feldspar-sericite-chlorite. Gold (mostly in the veins) is associated with elevated W-Bi and also As-Te-Sn, and not with iron enrichment or base metals, even though this system is proximal (~ 20 km) to IOCG and IOA deposits of the Coastal Cordillera. The main phase of gold mineralization occurred soon after emplacement of tonalitic dikes and granodiorite from the Relincho and Cuevitas plutons (U–Pb zircon between ~ 205 and 190 Ma), about 80 m.y. later than the development of orogenic fabrics. An absolute upper age limit is provided by compositionally distinct ore-cutting mafic dikes dated at 175–170 Ma (U–Pb apatite). The deposit falls into the intrusion-related gold category, as indicated by the cutting of earlier orogenic fabrics, the metal and alteration associations, and the spatial and temporal connection to reduced ilmenite-series intrusions, which are also very similar geochemically to the ‘type-locality’ IRG intrusions of the Tintina Belt in Yukon/Alaska. The El Zorro gold district represents the oldest and geologically western-most mineralizing event in the Central Andes of northern Chile, consistent with its time–space placement within the tectonic framework of easterly-younging mineralization and igneous activity in the Chilean Cordillera.

Knowledge, perception and ownership by local stakeholders among the world’s largest shark sanctuary a decade after its inception - Clémentine JM Séguigne; Mark E. Bond; Adeline Goyaud; Michael R. Heithaus; Gilles Siu; Zenya Rowe; Frédéric Torrente; Eric Clua (Marine Policy, 2025)

Comparing pollen and n-alkane carbon isotope records in a tropical lacustrine environment - Xennephone Hadeen; Cassandra Rowe; Michael Brand; Rainy Comley; Sourav Das; Christopher M. Wurster; Costijn Zwart; Michael I. Bird (Quaternary Science Reviews, 2025)

Traumatic Brain Injury in Mice Generates Early-Stage Alzheimer’s Disease Related Protein Pathology that Correlates with Neurobehavioral Deficits - Nicholas Panayi; Philip Schulz; Ping He; Brandon Hanna; Jonathan Lifshitz; Rachel K. Rowe; Michael R. Sierks (Molecular Neurobiology, 2024)
Traumatic brain injury (TBI) increases the long-term risk of neurodegenerative diseases, including Alzheimer’s disease (AD). Here, we demonstrate that protein variant pathology generated in brain tissue of an experimental TBI mouse model is similar to protein variant pathology observed during early stages of AD, and that subacute accumulation of AD associated variants of amyloid beta (Aβ) and tau in the TBI mouse model correlated with behavioral deficits. Male C57BL/6 mice were subjected to midline fluid percussion injury or to sham injury, after which sensorimotor function (rotarod, neurological severity score), cognitive deficit (novel object recognition), and affective deficits (elevated plus maze, forced swim task) were assessed post-injury (DPI). Protein pathology at 7, 14, and 28 DPI was measured in multiple brain regions using an immunostain panel of reagents selectively targeting different neurodegenerative disease-related variants of Aβ, tau, TDP-43, and alpha-synuclein. Overall, TBI resulted in sensorimotor deficits and accumulation of AD-related protein variant pathology near the impact site, both of which returned to sham levels by 14 DPI. Individual mice, however, showed persistent behavioral deficits and/or accumulation of toxic protein variants at 28 DPI. Behavioral outcomes of each mouse were correlated with levels of seven different protein variants in ten brain regions at specific DPI. Out of 21 significant correlations between protein variant levels and behavioral deficits, 18 were with variants of Aβ or tau. Correlations at 28 DPI were all between a single Aβ or tau variant, both of which are strongly associated with human AD cases. These data provide a direct mechanistic link between protein pathology resulting from TBI and the hallmarks of AD.

Trace metal and organic biosignatures in digitate stromatolites from terrestrial siliceous hot spring deposits: Implications for the exploration of martian life - Ema E. Nersezova; Michael C. Rowe; Kathleen A. Campbell; Andrew Langendam; Cherie Tollemache; Barbara Lyon; Amanda Galar; Diego M. Guido; Bronwyn L. Teece; Trinity L. Hamilton (Chemical Geology, 2024)

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Variability in surface CO2 flux: Implication for monitoring surface emission from geothermal fields - Tsung-Han Jimmy Yang; Isabelle Chambefort; Michael Rowe; Agnes Mazot; Anya Seward; Cynthia Werner; Tobias Fischer; Jun Seastres; Farrell Siega; Nick Macdonald; Thomas Brakenrig; Lauren Coup; et al. (Geothermics, 2024)

Vegetation changes through stadial and interstadial stages of MIS 4 and MIS 3 based on a palynological analysis of the Girraween Lagoon sediments of Darwin, Australia - Cassandra Rowe; Michael Brand; Christopher M. Wurster; Michael I. Bird (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Okataina Volcanic Centre, New Zealand: Magmatic, volcanological, structural, thermal, and geothermal evolution of an active caldera system—Introduction - Cornel E.J. de Ronde; Ery C. Hughes; Yasuo Ogawa; Michael C. Rowe (Journal of Volcanology and Geothermal Research, 2024)

Exploring the internal textures and physical properties of digitate sinter in hot springs: Implications for remote sampling on Mars - Ema E. Nersezova; Michael C. Rowe; Kathleen A. Campbell; Andrew Ang; Steve Matthews; Steven W. Ruff; Ashok Meghwal; Ludmila Adam; Niamh Galligan; Thomas Loho (Planetary and Space Science, 2023)

Guidelines for the selection of corrosion resistant alloys for CCS and CCUS injection wells - Bruce Craig; Adam Rowe; Michael Warmack; Thomas E. Doll; Catherine Stevens; Kevin C. Connors (International Journal of Greenhouse Gas Control, 2023)

Adjacent and downstream effects of forest harvest on the distribution and abundance of larval headwater stream amphibians in the Oregon Coast Range - Adam Duarte; Nathan D. Chelgren; Jennifer C. Rowe; Christopher A. Pearl; Sherri L. Johnson; Michael J. Adams (Forest Ecology and Management, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Contributions of cancer treatment, comorbidities, and obesity to aging-related disease risks among non-Hodgkin lymphoma survivors - Krista Ocier; Sarah Abdelaziz; Seungmin Kim; Kerry Rowe; John Snyder; Vikrant Deshmukh; Michael Newman; Alison Fraser; Ken Smith; Christy Porucznik; Kimberley Shoaf; Joseph Stanford; et al. (Cancer Causes & Control, 2023)

Understanding caldera degassing from a detailed investigation at Lake Rotoiti, Okataina Volcanic Centre, New Zealand - Tsung-Han Jimmy Yang; Isabelle Chambefort; Agnes Mazot; Michael C. Rowe; Brad Scott; Nick Macdonald; Cynthia Werner; Tobias P. Fischer; Cornel E.J. de Ronde (Journal of Volcanology and Geothermal Research, 2023)

A sulfur and halogen budget for the large magmatic system beneath Taupō volcano - Max S. Sharpe; Simon J. Barker; Shane M. Rooyakkers; Colin J. N. Wilson; Isabelle Chambefort; Michael C. Rowe; C. Ian Schipper; Bruce L. A. Charlier (Contributions to Mineralogy and Petrology, 2022)
The transport and degassing pathways of volatiles through large silicic magmatic systems are central to understanding geothermal fluid compositions, ore deposit genesis, and volcanic eruption dynamics and impacts. Here, we document sulfur (S), chlorine (Cl), and fluorine (F) concentrations in a range of host materials in eruptive deposits from Taupō volcano (New Zealand). Materials analysed are groundmass glass, silicic melt inclusions, and microphenocrystic apatite that equilibrated in shallow melt-dominant magma bodies; silicic melt and apatite inclusions within crystal cores inferred to be sourced from deeper crystal mush; and olivine-hosted basaltic melt inclusions from mafic enclaves that represent the most primitive feedstock magmas. Sulfur and halogen concentrations each follow distinct concentration pathways during magma differentiation in response to changing pressures, temperatures, oxygen fugacities, crystallising mineral phases, the effects of volatile saturation, and the presence of an aqueous fluid phase. Sulfur contents in the basaltic melt inclusions (~ 2000 ppm) are typical for arc-type magmas, but drop to near detection limits by dacitic compositions, reflecting pyrrhotite crystallisation at ~ 60 wt. % SiO 2 during the onset of magnetite crystallisation. In contrast, Cl increases from ~ 500 ppm in basalts to ~ 2500 ppm in dacitic compositions, due to incompatibility in the crystallising phases. Fluorine contents are similar between mafic and silicic compositions (< 1200 ppm) and are primarily controlled by the onset of apatite and/or amphibole crystallisation and then destabilisation. Sulfur and Cl partition strongly into an aqueous fluid and/or vapour phase in the shallow silicic system. Sulfur contents in the rhyolite melts are low, yet the Oruanui supereruption is associated with a major sulfate peak in ice core records in Antarctica and Greenland, implying that excess S was derived from a pre-eruptive gas phase, mafic magma recharge, and/or disintegration of a hydrothermal system. We estimate that the 25.5 ka Oruanui eruption ejected > 130 Tg of S (390 Tg sulfate) and up to ~ 1800 Tg of Cl, with potentially global impacts on climate and stratospheric ozone.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Long-lived dacitic magmatic systems and recharge dynamics in the Jemez Mountains volcanic field, western USA - Jie Wu; Michael C. Rowe; Shane J. Cronin; John A. Wolff; Bin Fu (Contributions to Mineralogy and Petrology, 2022)
We examine the connected history of dacite-dominant volcanic rocks of the Tschicoma Formation, erupted between 5.5 and 2 Ma from the Jemez Mountains volcanic field, western USA. Zircon samples from two separate eruptions have continuous SHRIMP U–Pb age spectra spanning 0.84–1.08 Myr duration (3.12–3.96 Ma and 3.50–4.58 Ma, respectively), following an episode of zircon crystallization 0.28–0.50 Myr earlier (at 4.46 Ma and 4.86 Ma, respectively). Zircon chemical variations, as well as ubiquitous resorption textures that commonly show large core-rim age differences (up to 720–740 kyr), suggest that they grew in separate melt lenses. Zircons were likely stored at near-solidus or even sub-solidus conditions after crystallization, but may have been reactivated in response to at least four major magma recharge events every 300–400 kyr and smaller events in between. A cycle of zircon dissolution (from heating), recrystallization (during cooling), and storage repeated in different locations in the Tschicoma mush system throughout its lifespan; each recharge-induced heating stage may last for several hundred to more than a thousand years based on calculations of zircon dissolution. We envisage the melt lenses to be distributed in a crystal mush zone, coalescing into a single magma batch as magma recharge occurs shortly before eruption. Once active, increasing magma supply rates may trigger large-scale partial melting of the pre-existing mush and caldera-forming eruptions.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Integrating charcoal morphology and stable carbon isotope analysis to identify non-grass elongate charcoal in tropical savannas - Emma Rehn; Cassandra Rowe; Sean Ulm; Craig Woodward; Atun Zawadzki; Geraldine Jacobsen; Michael I. Bird (Vegetation History and Archaeobotany, 2022)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Monitoring wetland water quality related to livestock grazing in amphibian habitats - Kelly L. Smalling; Jennifer C. Rowe; Christopher A. Pearl; Luke R. Iwanowicz; Carrie E. Givens; Chauncey W. Anderson; Brome McCreary; Michael J. Adams (Environmental Monitoring and Assessment, 2021)
Land use alteration such as livestock grazing can affect water quality in habitats of at-risk wildlife species. Data from managed wetlands are needed to understand levels of exposure for aquatic life stages and monitor grazing-related changes afield. We quantified spatial and temporal variation in water quality in wetlands occupied by threatened Oregon spotted frog ( Rana pretiosa ) at Klamath Marsh National Wildlife Refuge in Oregon, United States (US). We used analyses for censored data to evaluate the importance of habitat type and grazing history in predicting concentrations of nutrients, turbidity, fecal indicator bacteria (FIB; total coliforms, Escherichia coli ( E. coli ), and enterococci), and estrogenicity, an indicator of estrogenic activity. Nutrients (orthophosphate and ammonia) and enterococci varied over time and space, while E. coli , total coliforms, turbidity, and estrogenicity were more strongly associated with local livestock grazing metrics. Turbidity was correlated with several grazing-related constituents and may be particularly useful for monitoring water quality in landscapes with livestock use. Concentrations of orthophosphate and estrogenicity were elevated at several sites relative to published health benchmarks, and their potential effects on Rana pretiosa warrant further investigation. Our data provided an initial assessment of potential exposure of amphibians to grazing-related constituents in western US wetlands. Increased monitoring of surface water quality and amphibian population status in combination with controlled laboratory toxicity studies could help inform future research and targeted management strategies for wetlands with both grazing and amphibians of conservation concern.

Rural–urban disparities in colorectal cancer survival and risk among men in Utah: a statewide population-based study - Charles R. Rogers; Brenna E. Blackburn; Matthew Huntington; Karen Curtin; Roland J. Thorpe; Kerry Rowe; John Snyder; Vikrant Deshmukh; Michael Newman; Alison Fraser; Ken Smith; Mia Hashibe (Cancer Causes & Control, 2020)

Sequencing and assembly of small RNAs reveal the presence of several begomoviruses, potyviruses, badnaviruses and mastreviruses in the sweet potato leaf virome in Barbados - Angela T. Alleyne; Cara Cummins; Kherie Rowe; Michael James; Dina L. Gutiérrez; Segundo Fuentes (Journal of Plant Pathology, 2019)

Paleomagnetic determination of the age and properties of the 1780–1800 AD dome effusion/collapse episode of Mt. Taranaki, New Zealand - Geoffrey A. Lerner; Shane J. Cronin; Gillian M. Turner; Michael C. Rowe (Bulletin of Volcanology, 2019)

Effect of cattle exclosures on Columbia Spotted Frog abundance - Michael J. Adams; Christopher A. Pearl; Thierry Chambert; Brome McCreary; Stephanie K. Galvan; Jennifer Rowe (Wetlands Ecology and Management, 2018)

Influence of porosity and groundmass crystallinity on dome rock strength: a case study from Mt. Taranaki, New Zealand - Edgar U. Zorn; Michael C. Rowe; Shane J. Cronin; Amy G. Ryan; Lori A. Kennedy; James K. Russell (Bulletin of Volcanology, 2018)

A geochemical approach to distinguishing competing tectono-magmatic processes preserved in small eruptive centres - Lucy E. McGee; Raimundo Brahm; Michael C. Rowe; Heather K. Handley; Eduardo Morgado; Luis E. Lara; Michael B. Turner; Nicolas Vinet; Miguel-Ángel Parada; Pedro Valdivia (Contributions to Mineralogy and Petrology, 2017)

Nestedness and species replacement along bathymetric gradients in the deep sea reflect productivity: a test with polychaete assemblages in the oligotrophic north‐west Gulf of Mexico - Carol T. Stuart; Solange Brault; Gilbert T. Rowe; Chih‐Lin Wei; Martine Wagstaff; Craig R. McClain; Michael A. Rex (Journal of Biogeography, 2017)
Aim To test the hypothesis that low productivity drives the nestedness component of β‐diversity in polychaetes at the deep‐sea floor. Location Western Gulf of Mexico. Methods We used A. Baselga's (2010, Global Ecology and Biogeography, 19 , 134–143) metrics of species replacement and nestedness to assess their overall significance with differences in depth and particulate organic carbon ( POC ) flux to the seafloor. We used M. A. Rodríguez‐Gironés & L. Santamaría's (2006, Journal of Biogeography , 33 , 924–935) BINMATNEST to calculate the significance and direction of nestedness with depth and POC flux. Results Nestedness was the most significant part of β‐diversity with depth and POC flux. The rank order of nestedness increased significantly with increasing depth, and decreased significantly with increasing POC flux. There was little endemism below 2000 m. Main conclusion The polychaete fauna in the deepest western Gulf of Mexico is largely a nested subset of the shallower upper to mid‐bathyal fauna. While the causes of β‐diversity in the deep sea are undoubtedly multivariate, the relative importance of turnover and nestedness appears to be modulated by productivity in the form of POC flux to the seafloor. Under circumstances of extremely low POC flux and animal density in the deepest reaches of the Gulf, nestedness may be caused by some populations being maintained by immigration from larger populations upslope, or by biogeographic filtering for tolerance to abyssal conditions. Resources at great depths in regions of exceptionally low productivity may be too limited to permit adaptation resulting in endemism and continued downslope turnover. If productivity helps to explain the nestedness part of β‐diversity, this may lead to a more unified theory of deep‐sea biodiversity.

Synthesis and antimicrobial studies of azomethine and N-arylamine derivatives of 4-(4-formyl-3-phenyl-1H-pyrazol-1-yl)benzoic acid as potent anti-methicillin-resistant Staphylococcus aureus agents - Jamarcus Brider; Trent Rowe; Danielle Jamie Gibler; Adam Gottsponer; Evan Delancey; Michael Drew Branscum; Allyn Ontko; David Gilmore; Mohammad A. Alam (Medicinal Chemistry Research, 2016)

Integrating legacy soil phosphorus into sustainable nutrient management strategies for future food, bioenergy and water security - Helen Rowe; Paul J. A. Withers; Peter Baas; Neng Iong Chan; Donnacha Doody; Jeff Holiman; Brent Jacobs; Haigang Li; Graham K. MacDonald; Richard McDowell; Andrew N. Sharpley; Jianbo Shen; et al. (Nutrient Cycling in Agroecosystems, 2016)

Magmatic–hydrothermal fluids and volatile metals in the Spirit Lake pluton and Margaret Cu–Mo porphyry system, SW Washington, USA - Alexander A. Iveson; James D. Webster; Michael C. Rowe; Owen K. Neill (Contributions to Mineralogy and Petrology, 2016)

Replenishment of volatile-rich mafic magma into a degassed chamber drives mixing and eruption of Tungurahua volcano - Madison L. Myers; Dennis J. Geist; Michael C. Rowe; Karen S. Harpp; Paul J. Wallace; Josef Dufek (Bulletin of Volcanology, 2014)

Continental‐scale assessment of genetic diversity and population structure in quaking aspen ( P opulus tremuloides ) - Colin M. Callahan; Carol A. Rowe; Ronald J. Ryel; John D. Shaw; Michael D. Madritch; Karen E. Mock (Journal of Biogeography, 2013)
Aim Quaking aspen ( P opulus tremuloides ) has the largest natural distribution of any tree native to North America. The primary objectives of this study were to characterize range‐wide genetic diversity and genetic structuring in quaking aspen, and to assess the influence of glacial history and rear‐edge dynamics. Location North America. Methods Using a sample set representing the full longitudinal and latitudinal extent of the species’ distribution, we examined geographical patterns of genetic diversity and structuring using 8 nuclear microsatellite loci in 794 individuals from 30 sampling sites. Results Two major genetic clusters were identified across the range: a south‐western cluster and a northern cluster. The south‐western cluster, which included two subclusters, was bounded approximately by the Continental Divide to the east and the southern extent of the ice sheet at the Last Glacial Maximum to the north. Subclusters were not detected in the northern cluster, despite its continent‐wide distribution. Genetic distance was significantly correlated with geographical distance in the south‐western but not the northern cluster, and allelic richness was significantly lower in south‐western sampling sites compared with northern sampling sites. Population structuring was low overall, but elevated in the south‐western cluster. Main conclusions Aspen populations in the south‐western portion of the range are consistent with expectations for a historically stable edge, with low within‐population diversity, significant geographical population structuring, and little evidence of northward expansion. Structuring within the south‐western cluster may result from distinct gene pools separated during the Pleistocene and reunited following glacial retreat, similar to patterns found in other forest tree species in the western USA . In aspen, populations in the south‐western portion of the species range are thought to be at particularly high risk of mortality with climate change. Our findings suggest that these same populations may be disproportionately valuable in terms of both evolutionary potential and conservation value.

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Impacts of atmospheric nitrogen deposition: responses of multiple plant and soil parameters across contrasting ecosystems in long‐term field experiments - Gareth K. Phoenix; Bridget A. Emmett; Andrea J. Britton; Simon J. M. Caporn; Nancy B. Dise; Rachel Helliwell; Laurence Jones; Jonathan R. Leake; Ian D. Leith; Lucy J. Sheppard; Alwyn Sowerby; Michael G. Pilkington; et al. (Global Change Biology, 2012)
Atmospheric nitrogen ( N ) deposition is a global and increasing threat to biodiversity and ecosystem function. Much of our current understanding of N deposition impacts comes from field manipulation studies, although interpretation may need caution where simulations of N deposition (in terms of dose, application rate and N form) have limited realism. Here, we review responses to simulated N deposition from the UKREATE network, a group of nine experimental sites across the UK in a diversity of heathland, grassland, bog and dune ecosystems which include studies with a high level of realism and where many are also the longest running globally on their ecosystem type. Clear responses were seen across the sites with the greatest sensitivity shown in cover and species richness of bryophytes and lichens. Productivity was also increased at sites where N was the limiting nutrient, while flowering also showed high sensitivity, with increases and declines seen in dominant shrub and forb species, respectively. Critically, these parameters were responsive to some of the lowest additional loadings of N (7.7–10 kg ha −1 yr −1 ) showing potential for impacts by deposition rates seen in even remote and ‘unpolluted’ regions of E urope. Other parameters were less sensitive, but nevertheless showed response to higher doses. These included increases in soil % N and ‘plant available’ KCl extractable N , N cycling rates and acid–base status. Furthermore, an analysis of accumulated dose that quantified response against the total N input over time suggested that N impacts can ‘build up’ within an ecosystem such that even relatively low N deposition rates can result in ecological responses if continued for long enough. Given the responses have important implications for ecosystem structure, function, and recovery from N loading, the clear evidence for impacts at relatively low N deposition rates across a wide range of habitats is of considerable concern.

Genetic analysis of avian influenza A viruses isolated from domestic waterfowl in live-bird markets of Hanoi, Vietnam, preceding fatal H5N1 human infections in 2004 - Samadhan J. Jadhao; Doan C. Nguyen; Timothy M. Uyeki; Michael Shaw; Taronna Maines; Thomas Rowe; Catherine Smith; Lien P. T. Huynh; Ha K. Nghiem; Diep H. T. Nguyen; Hang K. L. Nguyen; Hanh H. T. Nguyen; et al. (Archives of Virology, 2009)

A Rapid Method to Score Stream Reaches Based on the Overall Performance of Their Main Ecological Functions - David K. Rowe; Stephanie Parkyn; John Quinn; Kevin Collier; Chris Hatton; Michael K. Joy; John Maxted; Stephen Moore (Environmental Management, 2009)

Isolation and characterization of microsatellite primers for the Fragrant Orchid Gymnadenia conopsea (L.) R. Brown (Orchidaceae) - Victoria V. Campbell; Graham Rowe; Trevor J.C. Beebee; Michael J. Hutchings (Conservation Genetics, 2002)

Kinetics and Mechanism of Hydrolysis of Efavirenz - Michael B. Maurin; Susan M. Rowe; Karl Blom; Michael E. Pierce (Pharmaceutical Research, 2002)

Relationship between bisphosphonate concentration and osteoclast activity and viability - Dorothy J. Rowe; Lois A. Etre; Michael J. Lovdahl; Donald J. Pietrzyk (In Vitro Cellular & Developmental Biology - Animal, 1999)

Enhanced hydrogen peroxide sensitivity and altered stress protein expression in iron-starved Mycobacterium smegmatis - Michael D. Lundrigan; Jean E.L. Arceneaux; Wenming Zhu; B. Rowe Byers (BioMetals, 1997)

Resistance exercise training and the orthostatic response - John P. McCarthy; Marcas M. Bamman; Janice M. Yelle; Adrian D. LeBlanc; Roger M. Rowe; Michael C. Greenisen; Stuart M. C. Lee; Elisabeth R. Spector; Suzanne M. Fortney (European Journal of Applied Physiology, 1997)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)